2020
DOI: 10.1523/eneuro.0009-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic α-Synuclein Accumulation in Rat Hippocampus Induces Lewy Bodies Formation and Specific Cognitive Impairments

Abstract: Occurrence of Lewy bodies (LBs)/Lewy neurites (LNs) containing misfolded fibrillar a-synuclein (a-syn) is one of the pathologic hallmarks of memory impairment-linked synucleinopathies, such as Parkinson's disease (PD) and dementia with LBs (DLB). While it has been shown that brainstem LBs may contribute to motor symptoms, the neuropathological substrates for cognitive symptoms are still elusive. Here, recombinant mouse a-syn fibrils were bilaterally injected in the hippocampus of female Sprague Dawley rats, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…These data exclude a deficit which is due to a primary deficit in sensory perception nor execution of a motoric response per se , but rather a deficit in relative egocentric space. Cognitive deficits have only been modelled in AAV-h-aSYN or pre-formed fibrils (PFFs) injection models with limited success, e.g., spatial working and reference memory on the Morris water maze test when aSYN was overexpressed in the VTA and septum ( Hall et al, 2013 ) or following injection of PFFs into the hippocampus ( Kasongo et al, 2020 ). AAV-h-aSYN overexpression in both neonate mice and rats has generally led to the development of pathology, but not to robust deficits in non-motor domains ( Aldrin-Kirk et al, 2014 ; Delenclos et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data exclude a deficit which is due to a primary deficit in sensory perception nor execution of a motoric response per se , but rather a deficit in relative egocentric space. Cognitive deficits have only been modelled in AAV-h-aSYN or pre-formed fibrils (PFFs) injection models with limited success, e.g., spatial working and reference memory on the Morris water maze test when aSYN was overexpressed in the VTA and septum ( Hall et al, 2013 ) or following injection of PFFs into the hippocampus ( Kasongo et al, 2020 ). AAV-h-aSYN overexpression in both neonate mice and rats has generally led to the development of pathology, but not to robust deficits in non-motor domains ( Aldrin-Kirk et al, 2014 ; Delenclos et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the pathological accumulation of α-syn in the hippocampus may lead to cognitive impairment ( Regensburger et al, 2014 ; Kasongo et al, 2020 ; Zhang et al, 2022 ). Our research showed that compared with other groups, nuclear localization of α-syn caused DNA damage response in hippocampal neuron earlier, induced apoptosis and inflammatory reaction, thereby causing more rapid and serious cognitive impairment and motor impairment in mice.…”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein, also down-regulated in the CE-123 group, is a presynaptic protein that under physiological conditions associates with synaptic vesicle membranes and regulates synaptic vesicle trafficking 50 . However, increased levels of α-synuclein lead to formation of aggregates and produce a physiological defect in synaptic vesicle recycling, which is associated with compromised neurotransmission 51 , 52 and linked to Parkinson’s disease and other neurodegenerative diseases 50 , 53 . The GO terms cluster “receptor-mediated endocytosis” comprising of GO terms like synaptic vesicle recycling, synaptic vesicle transport, receptor internalization, etc., was one of the most prominent processes modulated by CE-123 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%